Why become teachers? Case study of undergraduates in the Faculty of Education, University of Colombo - Lakshman, Iresha M.; Wickramasinghe, P.D.V.K. (European Scientific Journal, ESJ, 2020)
This study aimed to understand the reasons that encouraged student teachers who are following the Bachelor of Education (B.Ed.) Degree at the Faculty of Education, University of Colombo to join the teaching profession. A purposive sample of thirty undergraduates were selected for study. Data gathering was done using semi-structured interviews. The reasons presented by the student teachers were categorized into intrinsic, extrinsic and altruistic reasons. Belief in one’s personal characteristics as being suited for a career in teaching and personal interest were among the intrinsic reasons identified. Extrinsic reasons included reasons such as admiration for the physical appearance of teachers, social position attributed to teaching as a ‘noble’ profession, secured job with an adequate income, opportunities offered for career advancement and benefits for a balanced family life. Altruistic reasons were among the least mentioned reasons. Some participants mentioned a desire to contribute towards the wellbeing of children. The study also found that joining the B.Ed. programme with the sole intention of securing a job could lead to the recruitment of less suitable (though qualified) individuals to the profession. The findings of this study could be used to increase the quality of the process of producing and recruiting teachers.